2023
DOI: 10.21203/rs.3.rs-3236354/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Simulation study of atmosphere-ionosphere variations driven by the eruption of Hunga Tonga-Hunga Ha'apai on 15 January 2022

Hiroyuki Shinagawa,
Yasunobu Miyoshi

Abstract: The volcano of Hunga Tonga-Hunga Ha’apai in Tonga erupted on 15 January 2022, generating severe disturbances in the atmosphere and the ionosphere. This event provided us with large amount of data of the atmosphere and the ionosphere, and various kinds of observational studies have been made. Recently several simulation studies have also been made to reproduce and understand the atmosphere-ionosphere variations driven by the volcanic eruption. Although the simulation studies have reproduced the global variation… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 84 publications
3
1
0
Order By: Relevance
“…The results indicated that the highest electron density was at an altitude of ∼280-350 km, as presented in Figure 12, and this is in line with the 3D tomography modeling applied at the height of the third ionospheric layer with an altitude of ∼300 km (Chapman, 1931). The results obtained in this study are consistent with those in the study by Shinbori et al (2022), which indicated that the electron density calculated as a function of time had and Miyoshi (2023). This alignment provides crucial validation for radio occultation data, thereby enhancing and fortifying our comprehension of TIDs at elevated altitudes.…”
Section: 1029/2023ja031806supporting
confidence: 89%
See 3 more Smart Citations
“…The results indicated that the highest electron density was at an altitude of ∼280-350 km, as presented in Figure 12, and this is in line with the 3D tomography modeling applied at the height of the third ionospheric layer with an altitude of ∼300 km (Chapman, 1931). The results obtained in this study are consistent with those in the study by Shinbori et al (2022), which indicated that the electron density calculated as a function of time had and Miyoshi (2023). This alignment provides crucial validation for radio occultation data, thereby enhancing and fortifying our comprehension of TIDs at elevated altitudes.…”
Section: 1029/2023ja031806supporting
confidence: 89%
“…Furthermore, the adaptability of 3D tomography extends to observing the effects of SW and LW at altitudes of up to ∼500 km. These observations align seamlessly with data acquired through radio occultation methods, where TIDs can reach up to ∼500 km altitude, as reported by Shinagawa and Miyoshi (2023). This alignment provides crucial validation for radio occultation data, thereby enhancing and fortifying our comprehension of TIDs at elevated altitudes.…”
Section: D Ionospheric Disturbancessupporting
confidence: 87%
See 2 more Smart Citations